UHPLC-MS/MS Analysis of Antibiotics Transfer and Concentrations in Porcine Oral Fluid after Intramuscular Application - Anna Gajda; Ewelina Nowacka-Kozak; Małgorzata Gbylik-Sikorska; Piotr Cybulski (MDPI AG, 2022)
The monitoring of antibiotic use in animals is a crucial element to ensure food safety. The main goal of this study was to analyse the distribution of selected antibiotics to porcine oral fluid, as well as to demonstrate that an oral fluid is an alternative to other biological matrices used in the control of antibacterials. Therefore, an animal study with pigs treated using seven different antibiotics was performed. Sulfadoxine (SDX) with trimethoprim (TRMP), lincomycin (LIN), tiamulin (TIAM), tylosin (TYL), amoxicillin (AMX) and penicillin G (PEN G) were injected intramuscularly to pigs, and concentrations of these analytes in the oral fluid were assessed. Ultra-high-performance liquid chromatography coupled with mass spectrometry (UHPLC-MS/MS) was used to quantify the analytes. On the first day of medication, the highest concentrations for SDX and TRMP at the level of 22,300 µg/kg and 14,100 µg/kg were found, respectively. The concentrations of LIN (10,500 µg/kg) and TIAM (7600 µg/kg) were also relatively high. The peak of TYL was recorded on the second day of drug administration. Most of the analytes were present in oral fluid for 30 days, apart from TYL, which was detected for 27 days. It was found that AMX and PEN G were quantified only for 5 and 8 days, respectively, at very low concentrations. It was found that oral fluid can be used for the verification of antibiotics on pig farms.